P340 PARADOXICAL DIVERGENCE BETWEEN RATE OF SURVIVAL AND QUALITY INDICATOR OF CARE IN MYOCARDIAL INFARCTION ACCORDING TO PNE–AGENAS (ITALIAN NATIONAL HEALTHCARE OUTCOMES PROGRAM). (18th May 2022) - Casolo, G; Del Meglio, J; Lilli, A; Canale, L; Christou, A; De Caro, F; Bertini, L
Abstract: Background: The Italian National Healthcare Outcomes Program (PNE – AGENAS) each year provides quality performance measures for our Hospitals. Some measures refer directly to hard events such as mortality, others are focused over procedures that should be related to subsequent events, including mortality. The rate of PCI performed within 48 hours (48h–PCI) in patients with acute myocardial infarction (AMI) is currently used as a performance measures. An arbitrary standard of 35–40% of 48h–PCI for patients with AMI is considered the goal for a satisfactory practice. Methods: We analyzed the PNE–AGENAS performance measures for the year 2020. Overall 1652 MI have been recorded in 2020 in Tuscany. We considered those Hospitals with > 100 AMI. We related the 30 day and one–year mortality with the 48h–PCI of the 20 Hospitals identified. Of these latter 13 are Hospitals with a 24h PCI service. Results: All the hospitals hosting a catheterization laboratory largely overcame the 48h–PCI quality standard although with a wide variation among sites (70, 8 – 90.4%). On the contrary all the Hospitals without a cath–lab did not even approach the standard (0–33.%). The analysis of the mortality data both at 30 day and at 1 year showed a wide variability among Hospitals without an appreciable difference. The 30–day mortality rate ranged from 2 to 15% without any relationship with the 48h–PCI. In some cases better survival rates were recorded for those Hospitals with the worse 48h–PCI. Conclusions: Several factors makes 48h–PCI a useless and even confounding measure of performance. As a matter of fact this measure does not consider the type of MI treated (STEMI vs NSTEMI), nor the presence or not of a cath lab. Also it does not take account for the case mix of the population of AMI treated. Patients with STEMI represents about 30% of the activity of an Hospital with a 24h cath –lab. It is obviously easy for such an Hospital to satisfy the proposed standard as these patients should receive their PCI well before 24 hours. The contemporary organizations do cooperate and are organized as networks. The 48h–PCI should be only used to evaluate these networks, not the single hospitals. In conclusion our analysis by showing the divergent and paradoxical phenomena of better or similar survival in spite of longer or similar 48hPCI highlights the need to abandon this useless and even confounding measure to evaluate the Cardiology practice in the Italian Hospital.